Pengaruh Electronic Word of Mouth Terhadap Keputusan Pembelian Menggunakan Zomato di CafÃ© Koi The, Mall Kelapa Gading Jakarta Utara - Ricky Andrean; Sofiani Sofiani (Departemen Pariwisata Universitas Negeri Padang, 2023)
The development of internet resulted high growth of applications in Indonesia, which then used by business owners in marketing. Restaurant directory applications is gaining popularity for the ease of obtaining information, but information can also obtain using social media, which begun to use as marketing platform, but social media tends to bias in reviews. This study aims to examine whether there is influence between Electronic Word of Mouth on Zomato on purchasing decisions. Electronic word of mouth is information from the results of the assessment of various aspects of product by consumers, can be called online reviews. Purchasing decisions are when consumers faced with two or more possiblities that have been reached by consumers after various considerations. The sample of this study obtained by slovin technique which resulted 100 people, this research is quantitative study, with non-probability technique. The results of this study indicate that electronic word of mouth has effect on purchasing decisions. The conclusion of this study is the dimensions of Electronic Word of Mouth is Intensity, Content, and Valance of Opinion has positive influence on purchasing decisions. Suggestions for further research is add other independent variables, and for the business, this can be used as evaluation because there was influence between e-wom on purchasing decisions.